Harmonious project and program management in a changing environment - A. V. Pletnyova; E. A. Khalimon (Вестник университета)
Constantly changing environmental conditions, in addition to the lack of resources, are one of the biggest obstacles in the implementation of various projects and programs. Currently, companies associated with project management are trying to identify approaches that will allow them to effectively manage projects and programs in an unstable environment. The article examines such promising approaches to project management as sustainable, “green”, value-based project management. The paper analyses the experience of foreign and domestic companies in applying these approaches in their activities. The authors define the main methodological recommendations and standards on the basis of which project management is carried out within the framework of these approaches.